Coercive or discursive: a critical study of carceral dystopian society in Bina Shah’s Before She Sleeps - Salman Ali,; Malik Haroon Afzal, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The term dystopia describes a society where all conditions appear to be working against individuals. The concept of dystopia has been present since time immemorial. However, the previous century of world wars, natural disasters, and the worst human conditions like pandemics, famine, and mass atrocities make it more complex in today’s world. This study investigates Bina Shah’s novel Before She Sleeps of dystopian account through the theoretical framework of Michel Foucault’s concepts of panopticism and carceral society while contesting the panoptical nature of power. It carefully observes the selected text by focusing on how surveillance mechanisms, power structures, and punitive procedures align with Foucault’s ideas of coercive and discursive power structures in relation to dystopian fiction’s ability to offer a sight of subversion and negotiation. However, a keen examination of novel’s plot and characters reveals that the Green City—which represents power—substantiates its role as a coercive agency exercising its control by means of social institutions, but at the same time it goes against Foucault’s idea which says, ‘power is discursive’, especially when we come across the structure of Panah (an illegal safe-haven for rebel women). It also highlights the ability of dystopian genre to offer a sight of subversion and negotiation by creating strong and rebellious characters, such as the women of Panah, even in the face of acute coercion and censorship. This exploration adds to a profound comprehension of dystopian writing and its importance in the contemporary discourse on oppressive society, authoritarian government and the misuse of advanced technology.